Life Card Sebagai Media Pengembangan Pemahaman Diri Siswa di MAN 1 Kebumen - Ike Putri Nurandini; Bunga Sari Meiliana; Mei Maulina; Nida Nur Aniqo; Kholil Lur Rochman (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
Self-understanding is something that every individual must have. In its application, self-understanding is not only to help individuals in increasing self-confidence, but can also help individuals in all aspects of their society. Self-understanding can be known through anything, such as one of the media used by PPL students at MAN 1 Kebumen, they apply self-understanding through Life Cards in which there are several questions and statements that will be answered by students. This can certainly help them to open up more, recognize their potential, and develop their life skills. The application of this media is applied to students in class X and class XI. The method used in this study is qualitative research. As a result of the implementation of self-acceptance through Life Card at MAN 1 Kebumen in class X and XI, there are 172 students who can understand themselves, and there are 59 students who cannot even understand themselves at all.